Rancang Bangun Sistem Penjualan Furniture Berbasis Web Dengan Metode Prototype - Gina Apriasiska; Juni Nurma Sari (Politeknik Caltex Riau, 2022)
Edi Furniture is a business that is engaged in furniture and furniture and has been running for about 30 years. Many buildings such as schools, health centers, police houses, and other buildings have furniture and furniture made in Edi Furniture. Many contractors are already clients of Edi Furniture. However, payments and data processing are still done manually. That way we need a system that can process the furniture sales process online, can provide information from wood processing to completion, and process data obtained from the sales process in the form of order reports, payment reports, product reports, and Inventory reports. The solution to this problem is the construction of a system